A Comparative Study in Final Project Implementation of Indonesia and Brunei Darussalam - Annindita Hartono Putri; Muhammad Jafar Shodiq; Fika Noor Muhammad; M. Aqil Arfan Bin Arjune (Journal of Innovation in Educational and Cultural Research, 2025)
This study explores the implementation of final projects in higher education systems in Indonesia and Brunei Darussalam to understand their role in shaping the student learning experience. Using a qualitative approach, data were collected through observation, interviews, and document analysis, followed by data condensation, presentation, and conclusion drawing. The findings highlight how academic policies shape the forms and expectations of final projects. In Indonesia, undergraduate final projects are predominantly in the form of theses, while alternatives such as prototypes and projects are emerging depending on institutional policies. Master's and doctoral programs typically involve theses or dissertations. In Brunei, institutions adopt varied approaches: internships at KUPU SB and theses at UNISSA are common for undergraduates, with master's and doctoral programs offering flexibility between research-based theses and coursework. This study concludes that academic frameworks significantly influence student learning dynamics and outcomes. It contributes to educational research by providing insights into the relationship between institutional practices and higher education learning experiences.